Integrating the Whole Language Approach in Multicultural Education: Developing Reading Comprehension Skills and Cross-Cultural Awareness in Elementary School Students - Hasyda, Suryadin; Putrayasa, Ida Bagus; Sudiana, I Nyoman (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2023)
The purpose of this study is to analyze the integration of the whole language approach in multicultural education for third grade students at SD Muhammadiyah 2 Kota Kupang in the 2022/2023 academic year. This classroom action research consisted of four stages in each cycle: planning, action, observation, and reflection. The subjects were 25 third grade students at SD Muhammadiyah 2 Kota Kupang. In cycle 1, the percentage of students reaching mastery learning was 20% with 5 students succeeding. In cycle 2, the percentage increased to 92% with 23 students succeeding. From cycle 1 to cycle 2 there was an improvement that met the success indicators. Thus this classroom action research was successful, indicating that implementing the whole language approach can improve students' reading comprehension skills. The whole language approach is used as a key instrument in multicultural education, helping to develop a generation that is not only literate but also able to appreciate and positively interact with various cultures.